Pengabdian Mahasiswa MBKM: Mewujudkan Lingkungan Bersih dan Hijau di MTs Muslimat NU - Krisna Dwi Alifhia Rezky; Akhmad Ali Mirza (Lembaga Pengembangan Kinerja Dosen, 2024)
This community service program is part of the Merdeka Belajar Kampus Merdeka (MBKM) initiative, aiming to create a clean and green environment at MTs Muslimat NU through drainage cleaning and flower planting activities. The program involved teachers and university students as the main participants, without the direct involvement of students. Its primary focus is to raise awareness about the importance of environmental cleanliness and greening efforts to preserve ecosystems. The drainage cleaning was carried out to prevent blockages that could lead to flooding, while flower planting aimed to beautify the school environment and educate participants about the benefits of greening. Through the active involvement of teachers and students, this program is expected to foster positive habits in maintaining cleanliness and environmental sustainability. Additionally, it promotes the value of mutual cooperation, which can be continued by the entire school community to create a healthy and comfortable environment. Supported by the MBKM program, similar initiatives are expected to expand their impact, engage more stakeholders, and contribute significantly to sustainable environmental conservation efforts.